Human Properdin Released By Infiltrating Neutrophils Can Modulate Influenza A Virus Infection - Varghese, Praveen M.; Mukherjee, Shuvechha; Al-Mohanna, Futwan A.; Saleh, Souad M.; Almajhdi, Fahad N.; Beirag, Nazar; Alkahtani, Saad H.; Rajkumari, Reena; Nal Rogier, Beatrice; Sim, Robert B.; Idicula-Thomas, Susan; Madan, Taruna; et al. (Frontiers in Immunology, 2021)
The complement system is designed to recognize and eliminate invading pathogens via activation of classical, alternative and lectin pathways. Human properdin stabilizes the alternative pathway C3 convertase, resulting in an amplification loop that leads to the formation of C5 convertase, thereby acting as a positive regulator of the alternative pathway. It has been noted that human properdin on its own can operate as a pattern recognition receptor and can exert immune functions outside its involvement in complement activation. Properdin can bind directly to microbial targets via DNA, sulfatides and glycosaminoglycans, apoptotic cells, nanoparticles, and well-known viral virulence factors. This study was aimed at investigating the complement-independent modulation of properdin against Influenza A virus infection. Being the first immune cells to arrive at the site of IAV infection, we show here that IAV challenged neutrophils released properdin in a time-dependent manner. Properdin can directly interact with HA, NA and M1 Influenza A virus proteins in ELISA and western blot. In an infection assay using A549 cells, properdin suppressed viral replication in pH1N1 while promoting replication of H3N2, as revealed by qPCR analysis of M1 transcripts. Properdin treatment triggered an anti-inflammatory response in H1N1-challenged A549 cells and a pro-inflammatory response in H32N2-infected cells, as evident from differential mRNA expression of TNF-α, NF-kB, IFN-α, IFN-β, IL-6, IL-12 and RANTES. Properdin treatment also reduced luciferase reporter activity in MDCK cells transduced with H1N1 pseudotyped lentiviral particles; however, it was increased in the case of H3N2 particles. Modelling studies revealed that properdin could bind HA and NA of the H1N1 subtype with higher affinity compared to H3N2 due to the presence of an HA cleavage site inH1N1. Collectively, we conclude that infiltrating neutrophils at the site of a lung infection can release properdin in the presence of IAV, which then acts as an entry inhibitor for pandemic H1N1 subtype while suppressing viral replication and inducing an anti-inflammatory response. H3N2 subtype can escape this immune restriction due to altered HA and NA, leading to enhanced entry, replication and pro-inflammatory response. Thus, depending on the subtype, properdin can either limit or aggravate IAV infection in the host.